Phytochemical Profile and Biological Activities of Crude and Purified Leonurus cardiaca Extracts - Simone Angeloni; Eleonora Spinozzi; Filippo Maggi; Gianni Sagratini; Giovanni Caprioli; Germana Borsetta; Gunes Ak; Kouadio Ibrahime Sinan; Gokhan Zengin; Sabrina Arpini; Giacomo Mombelli; Massimo Ricciutelli (Plants, 2021)
Leonurus cardiaca L. (Lamiaceae) is a perennial herb distributed in Asia and Southeastern Europe and has been used in traditional medicine since antiquity for its role against cardiac and gynecological disorders. The polar extracts obtained from L. cardiaca aerial parts contain several compounds among which alkaloids, iridoids, labdane diterpenes, and phenylethanoid glycosides play a major role in conferring protection against the aforementioned diseases. On the other hand, the antioxidant activities and the enzyme inhibitory properties of these extracts have not yet been deeply studied. On the above, in the present study, crude and purified extracts were prepared from the aerial parts of L. cardiaca and have been chemically characterized by spectrophotometric assays and HPLC-DAD-MS analyses. Notably, the content of twelve secondary metabolites, namely phenolic acids (chlorogenic, caffeic, caffeoylmalic and trans-ferulic acids), flavonoids (rutin and quercetin), phenylethanoid glycosides (verbascoside and lavandulifolioside), guanidine pseudoalkaloids (leonurine), iridoids (harpagide), diterpenes (forskolin), and triterpenes (ursolic acid), has been determined. Furthermore, the extracts were tested for their antioxidant capabilities (phosphomolybdenum, DPPH, ABTS, FRAP, CUPRAC, and ferrous chelating assays) and enzyme inhibitory properties against cholinesterase, tyrosinase, amylase, and glucosidase. The purified extracts contained higher phytochemical content than the crude ones, with caffeoylmalic acid and verbascoside as the most abundant compounds. A linear correlation between total phenolics, radical scavenging activity, and reducing power of extracts has been found. Notably, quercetin, caffeic acid, lavandulifolioside, verbascoside, chlorogenic acid, rutin, and ursolic acid influenced the main variations in the bioactivities found in L. cardiaca extracts. Our findings provide further insights into the chemico-biological traits of L. cardiaca and a scientific basis for the development of nutraceuticals and food supplements.